Antibacterial activity of toothpaste containing robusta coffee bean (Coffea canephora)extract towards Treponema denticola: a laboratory experimental study - Perdana, Mohammad Daffa Duta; Praharani, Depi; Sari, Desi Sandra (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACT Introduction: Treponema denticola is a Gram-negative anaerobic bacterium that causes periodontal disease and is dominant in subgingival plaque. Periodontal disease can be prevented by mechanical plaque control, such as brushing teeth with toothpaste. One of the herbal ingredients that can be used as an additional ingredient for toothpaste is robusta coffee beans which contain active antibacterial compounds. The aim of this research was to analyze the antibacterial activity of toothpaste containing Robusta coffee bean extract at concentrations of 12.5, 25, and 50% against T. denticola. Methods: The type of research used is experimental with a research design using a posttest only control group design. Robusta coffee beans were extracted using the maceration method, and formulated into toothpaste with concentrations of 12.5, 25, and 50%. The well diffusion method with Mueller-Hinton Agar (MHA) media which had been inoculated with T. denticola was used for the antibacterial activity test. The research group consisted of toothpaste with 12.5% robusta coffee bean extract group, 25% group, and 50% group, as well as the positive control and negative control groups. Results: The inhibitory zone was formed in the toothpaste with 12.5% robusta coffee bean extract group, 25% group, 50%, and positive control group against the growth of T. denticola. The average diameter of the inhibition zone produced respectively from the lowest to the highest concentration of robusta coffee bean extract were 11.02 mm, 12.81 mm, and 15.95 mm, with significant differences between concentrations (p<0,05). Conclusion: Toothpaste containing robusta coffee bean extract at concentrations of 12.5, 25, and 50% showed the antibacterial activity against T. denticola. Toothpaste containing 50% of the robusta coffee bean extract showed the greatest antibacterial activity.KEY WORDS: robusta coffee bean, antibacterial, toothpaste, treponema denticola, periodontal diseaseDaya antibakteri pasta gigi yang mengandung ekstrak biji kopi robusta (coffea canephora) terhadap treponema denticola: Studi eksperimentalABSTRAK Pendahuluan: Treponema denticola merupakan bakteri anaerob Gram negatif penyebab penyakit periodontal dan dominan pada plak subgingiva. Penyakit periodontal dapat dicegah dengan pengendalian plak secara mekanis, seperti menyikat gigi dengan pasta gigi. Salah satu bahan herbal yang dapat dimanfaatkan sebagai bahan tambahan pasta gigi adalah biji kopi robusta yang mengandung senyawa aktif antibakteri. Tujuan penelitian ini adalah untuk menganalisis daya antibakteri pasta gigi yang mengandung ekstrak biji kopi robusta pada konsentrasi 12,5%, 25%, dan 50% terhadap T. denticola. Metode: Jenis penelitian yang digunakan yaitu eksperimental laboratorium dengan rancangan penelitian menggunakan the post test only control group design. Biji kopi robusta diekstraksi menggunakan metode maserasi, dan diformulasi menjadi pasta gigi dengan konsentrasi 12,5, 25 dan 50%. Uji antibakteri menggunakan metode difusi sumuran dengan media Mueller-Hinton Agar (MHA) yang telah diinokulasi T. denticola. Kelompok penelitian terdiri dari kelompok pasta gigi dengan ekstrak biji kopi robusta konsentrasi 12,5, 25, dan 50%, kontrol positif, dan kontrol negatif. Hasil: Terbentuk zona hambat pada kelompok pasta gigi yang mengandung ekstrak biji kopi robusta konsentrasi 12,5, 25, dan 50%, dan kontrol positif terhadap pertumbuhan T. denticola. Rata-rata diameter zona hambat yang dihasilkan berturut-turut dari konsentrasi ekstrak biji kopi robusta terendah hingga tertinggi adalah 11,02 mm; 12,81 mm; dan 15,95 mm dengan perbedaan yang signifikan di antara tiap konsentrasi (p<0,05). Simpulan: Pasta gigi yang mengandung ekstrak biji kopi robusta konsentrasi 12,5, 25, dan 50% memiliki daya antibakteri terhadap T. denticola. Pasta gigi dengan konsentrasi ekstrak 50% memperlihatkan daya antibakteri yang paling besar.KATA KUNCI: biji kopi robusta, antibakteri, pasta gigi, treponema denticola, penyakit periodontal